Design and Development of an Automobile Brake Lining Monitoring System - Sivarao, Subramonian; Taufik (2007)
The braking system is the most important automobile which generally fulfills the aim to stop a vehicle on the road. In the olden days it was also one of the simplest. Over the years as improvement have been made, the system that has evolved isn’t so simple anymore. This study will focus on the redesigning & development of brake lining monitoring system which suits Malaysian made car namely Proton Perdana V6. Critically, this investigation is to detect the brake lining wear limit so that when the lining is about to go beyond the safety limit, an indication will be sent to the dash panel, where, the driver will be alerted about it. A test rig has been developed to run the testing and validate the findings dynamically.